Indicadores de Bem-estar Humano para Povos Tradicionais: o caso de uma comunidade ribeirinha na fronteira da Amazônia brasileira - Luiz Felipe Barbosa Lacerda (Universidade do Vale do Rio dos Sinos (UNISINOS), 2017)
The paper presents an innovative way of how to create and apply Human Wellbeing Indicators. The paper starts with a historical analysis of how those indicators were created and finishes with a set of indicators self-determined by Amazonian indigenous and riverine people themselves. The set of indicators is based on the concept of abundance as the concept that identifies indigenous and riverine people’s wellbeing. The set of Human Wellbeing Indicators for Traditional Societies presented is supported in five main capacities: collective control of territory, autonomous cultural agency, food security guarantee, the construction of a peaceful environment to live in, and self-care and reproduction. The set of Human Wellbeing Indicators for Traditional Societies was applied in the riverine community of São José, located in the Benjamin Constant municipality, in the triple border between Brazil, Colombia and Peru, as a result of an international scientific cooperation process between the Education and Amazonian Diversity research group of the Estado do Amazonas University of Brazil (GPEDA-UEA) and the Traditional Knowledge Value research group of the Instituto Amazónico de Investigaciones Científicas SINCHI of Colombia. The experience shared the methodological advances on the construction of precise indicators for traditional societies and showed how traditional communities build up their wellbeing in relation to the knowledge they have of water, soil and forest cycles, making them autonomous in the productive and cultural processes of their territories.